Rapid activation of tumor-associated macrophages boosts preexisting tumor immunity - Hoves, Sabine (J Exp Med, 2018)
Depletion of immunosuppressive tumor-associated macrophages (TAMs) or reprogramming toward a proinflammatory activation state represent different strategies to therapeutically target this abundant myeloid population. In this study, we report that inhibition of colony-stimulating factor-1 receptor (CSF-1R) signaling sensitizes TAMs to profound and rapid reprogramming in the presence of a CD40 agonist before their depletion. Despite the short-lived nature of macrophage hyperactivation, combined CSF-1R+CD40 stimulation of macrophages is sufficient to create a proinflammatory tumor milieu that reinvigorates an effective T cell response in transplanted tumors that are either responsive or insensitive to immune checkpoint blockade. The central role of macrophages in regulating preexisting immunity is substantiated by depletion experiments, transcriptome analysis of ex vivo sorted TAMs, and gene expression profiling of whole tumor lysates at an early treatment time point. This approach enabled the identification of specific combination-induced changes among the pleiotropic activation spectrum of the CD40 agonist. In patients, CD40 expression on human TAMs was detected in mesothelioma and colorectal adenocarcinoma.